Impact of Adolescents’ Family Meal Eating Patterns upon their Weight Control Behaviors at Secondary Schools in Baghdad City - basheer, buthaina; Ma΄ala Eqbal (Iraqi National Journal of Nursing Specialties, 2015)
Objective: The study aimed to identify the adolescents’ family meal eating patterns, and find out the relationship between adolescents’ family meal eating patterns and their weight control behaviors. Methodology: A descriptive study was conducted on impact of adolescents’ family meal eating patterns upon their weight control behaviors in secondary schools at Baghdad city, starting from 20th of April 2013 to the end of October 2014. Non- probability (purposive) sample of 1254 adolescents were chosen from secondary schools of both sides of Al-Karkh and Al-Russafa sectors. Data was collected through a specially constructed questionnaire format include (54) items multiple choice questions. The validity of the questionnaire was determined through a panel of experts related to the field of the study, and the reliability through a pilot study. The data were analyzed through the application of descriptive statistical analysis frequency, & percentages, and inferential statistical analysis, chi-square, are used. Results: The study results revealed the study sample mostly (38.4%, 40.3%, 40.3%, 31.4%, 38.5%, 41.4%, and 33.1%) always and sometimes eat meals rich with fat, carbohydrate and sweetly elements shown that in breakfast meal like fried eggs, fried vegetables and cream, better with jam, while in lunch and dinner mostly the adolescents and their family (41.0%, 67.2%, 55.7%, 37.7%, 52.5%, 41.3%, 32.3%, 41.2%, and 31.4%) sometimes interest bringing and eating burger, shawerma and falafel sandwich from out, also half percent the study sample sometimes eating healthy foods like cooking and fresh colure vegetables at home, more than one third and half of them (37.4%)and (38.1%)daily and sometimes eat fast food in or out home. The study sample eating habits with the family at home, eating snacks, fast food in and out home, have highly significant association with their total weight control behaviors methods. Recommendation: The study recommended that should adolescents’ family have more intervention to follow regular mealtime and eating healthy foods to prevent and protect them from excessive risk weight gain at future.